CONTRASTING MEANINGS IN ENGLISH AND UZBEK LINGUOCULTURES: OXYMORONS AND THEIR TRANSLATION CHALLENGES - Muattar Temirova (TADQIQOTLAR, 2025)
Abstract. This article analyzes into the comparative analysis of oxymorons as a stylistic  device  within  English  and  Uzbek  linguocultures.  It  explores  how  these paradoxical expressions, which juxtapose contradictory terms, reflect cultural nuances and  cognitive  frameworks  specific  to  each  language.  The  study  highlights  the significant  challenges  translators  face  when  attempting  to  convey  the  intended meaning, stylistic effect, and cultural resonance of oxymorons from one language to another.  Drawing  upon  principles  of  contrastive  linguistics,  translation  theory,  and cultural  semantics,  the  article  examines  various  scholarly  opinions  and  provides illustrative  examples  to  demonstrate  the  complexities  involved.  It  argues  that successful translation of oxymorons requires not only linguistic proficiency but also a deep understanding of the source and target linguocultures to navigate the conflicting meanings effectively.